Newly Graduated Physical Education Teachers' Experiences of and Readiness for Professional Practice: A Scoping Review - Ingrid Birkelund; Per Midthaugen; Jorunn Spord Borgen (Cappelen Damm Akademisk NOASP, 2024)
This scoping review examines previously published research on newly graduated physical education (PE) teachers in an effort to describe the scope and types of the empirical studies, perspectives and understandings concerning this population's experiences of and readiness for the performative and organisational aspects of professional practice. Following an initial review of 71 studies, a total of 16 published studies were found to be eligible for inclusion in the review. A five-step qualitative content analysis then identified the important features of the data related to the stated aim of the review. Prior studies determined newly graduated PE teachers to be qualified in their field, although their professional practice depends on other people's participation and cooperation within the school environment. A problem-oriented trend was observed in the research data when newly graduated PE teachers were asked to elaborate on their experiences. Moreover, a knowledge gap was identified in terms of newly graduated PE teachers and their varied experiences of the induction phase of their professional practice.